Rock Types Classification and Distribution on Anabanua Village, Barru Regency, South Sulawesi - Muhammad Resky Ariansyah; Muhammad Fawzy Ismullah Massinai; Muhammad Altin Massinai (Universitas Muslim Indonesia, 2020)
Anabanua Village, Barru Regency is one of the areas in South Sulawesi that has quite unique geological conditions. This condition inseparably comes from the complicated geological process that took place during the formation of the island, Sulawesi. In Anabanua Village, there are many types of rocks such as sedimentary rocks, metamorphic rocks and igneous rocks. This paper aims to map and classify the types of rock by taking samples on different places in the research area. Then we observe the samples physical properties. The results showed, from taking 10 rock samples in different places, they have various characteristics. 8 of them were sedimentary rocks, they are Limestone Quartz, Limestone Sand, Shale, Sandstone, Coal, Limestone Bioturbation, Breccia, and Chert Stone. The other 2 samples were metamorphic rocks, they are Greenschist and Quartzite.